Intrapartum Diagnosis and Treatment of Longitudinal Vaginal Septum - Antonio Henriques de França Neto; Bianca Virgolino Nóbrega; Jessé Clementino Filho; Tiago Cavalcanti do Ó; Melania Maria Ramos de Amorim (Hindawi Limited, 2014)
Longitudinal vaginal septum is a rare Müllerian malformation that may be associated with dyspareunia, dysmenorrhea, primary amenorrhea, and infertility. In this report, the authors present a case of longitudinal vaginal septum in a 15-year-old patient with a full-term pregnancy whose diagnosis was only made during labor following bidigital vaginal and speculum examination. Septoplasty was performed during the second stage of labor. Both mother and child progressed satisfactorily and were discharged from hospital in good health. Six months later, ultrasonography, hysterosalpingography, and hysteroscopy were carried out and no other associated abnormality was found.